A novel approach to frequency support in a wind integrated power system. (August 2017) - Deepak, M.; Abraham, Rajesh Joseph; Gonzalez-Longatt, Francisco M.; Greenwood, David M.; Rajamani, Haile-Selassie
Abstract: This paper discusses the impact of wind penetration on frequency control of a thermal dominated system considering Generation Rate Constraints (GRC) and dead band non-linearities. The hidden inertia emulation and coordinated operation of conventional power generation systems with wind energy can effectively alleviate the frequency excursions during sudden load disturbances. Conventional energy storage device like Flywheel Energy Storage (FES) system can be used in conjunction with wind integrated power system to overcome the intermittent nature of power generation. Thyristor Controlled Series Compensator (TCSC) is found to be effective in damping low frequency oscillations in weak tie-lines and supplement the frequency regulation. A stochastic population based evolutionary computation technique - Particle Swarm Optimization (PSO) is used to tune the controller gains. A strategy comprising inertia control, coordinated operation of conventional generation units with wind energy and TCSC-FES has been proposed to enhance the frequency regulation which is effective in controlling low frequency oscillations as established by the simulation results. Highlights: A modelling approach enabling the simulation of dynamic frequency events in a multi-area power system with wind penetration. Proposal of a FES system to improve primary frequency regulation in a power system with high wind penetration. A combined frequency control scheme using FES, TCSC, and conventional generation.